COLOR IN PAINTING (AJANTA): चित्रकला में रंग (अजन्ता) - Kumar, Dilip (International Journal of Research -GRANTHAALAYAH, 2014)
Depiction of murals in the caves of Anjanta has been made from the period of 200 BC to 620 AD, after such a long interval, the character beauty and salt of some of the pictures of the paintings have decreased, yet till date the aura of the paintings of Ajanta has not faded. . In the paintings of Ajanta, beautiful characters are seen here and there is vikhari. Although the brightness of these paintings has faded enough, the colors appear to be life-threatening. The shiny bottom, green and purple color still glows in its former aura. The colors of the body and the clothes are lavish and consistent, except for some early paintings of Ajanta, in the sixteenth and seventeenth caves, the painters of Ajanta have shown a tendency to draw figures in light letters on the dark background, but on the other hand dark shapes on the dark background. The tendency to make K is also seen which is similar to the Venetian-painting style of Europe. The painter was very conscious to attract the attention of the viewer to the picture, due to this he has used black color in the hair of human figures, which has increased the form and elegance and produced the desired effect. अंजन्ता की गुफाओं मे भिति चित्रण 200 ई0 पू0 से लेकर 620 ई0 तक के समय तक बनायी गयी है इतने लम्बे समय अन्तराल के बाद कुछ भिति चित्रों के वर्ण सौष्ठव तथा लवण्य कम हुये है फिर भी आज तक अजन्ता के चित्रों की आभा फीकी नही पडी है। अजन्ता के चित्रों में सुन्दर वर्ण छटा यत्र-तत्र विखरी दिखाई पडती है। यद्यपि इन चित्रों की चमक पर्याप्त धूमिल पड चुकी है तथापि रंग जानदार प्रतीत होते है। चमकदार नीचे, हरे तथा बैगनी रंग अपनी पूर्व आभा में आज भी जगमगाते है। शरीर तथा कपडों का रंग लावण्य युक्त और संगत हैं अजन्ता के कुछ आरम्भिक चित्रों को छोडकर सोलहवीं तथा सत्रहवी गुफा में अजन्ता के चित्रकारों ने गहरी पृष्ठ भूमि पर हल्के वर्ण विधान में आकृतिया बनाने की प्रवृति दिखाई है, परन्तु दूसरी ओर हल्की पृष्ठ भूमि पर गहरी आकृतियों के बनाने के प्रवृति भी दिखाई पडती है जो यूरोप की वेनिस-चित्रकला शैली के समान है। चित्रकार दर्शक के ध्यान को चित्र की ओर आकृष्ट करने के लिये बहुत जागरूक रहा, इस कारण उसने मानवाकृतियों के बालों में काले रंग का प्रयोग किया है, जिससे रूप और लावण्य की वृद्धि हुई है और इच्छित प्रभाव उत्पन्न हो गया है।